PENERAPAN METODE BIMBINGAN KELOMPOK BELAJAR UNTUK MENINGKATKAN DISIPLIN DIRI DAN PRESTASI BELAJAR - Jannatul Hikmah (UNIB Press, 2022)
This study aims to describe the application of group tutoring and the effectiveness of group tutoring in order to improve self-discipline and learning achievement. The research method used is Classroom Action Research and uses quasi-experiments. The subjects of this study were students of class X SMA Negeri 1 Kikim Timur Semester 2 of the 2020/2021 academic year. The number of students for the PTK class, namely class X.2, amounted to 35 people, for the experimental class, namely X.1, which amounted to 35 people and for the control class, namely X.3, which amounted to 35 people. The method used in data collection in this study used group guidance observation sheets, disciplinary observation sheets, and student learning outcomes tests. Data analysis used average score analysis and test-test. Which consisted of a different test between cycles and an unrelated two-sample difference test. The results showed that the application of group tutoring can improve student self-discipline, student learning achievement and the effectiveness of the application of group guidance in class X craft subjects at SMA Negeri 1 Kikim Timur